Should maternal anesthesia delay breastfeeding? A systematic review of the literature - Oliveira, Morenna Ramos E; Santos, Murillo Gonçalves; Aude, Débora Alves; Lima, Rodrigo Moreira E; Módolo, Norma Sueli Pinheiro; Navarro, Lais Helena (Sociedade Brasileira de Anestesiologia, 2019)
AbstractIntroduction: The importance and benefits of breastfeeding for the babies and mothers are well established and documented in the literature. However, it is frequent that lactating mothers need to undergo general or spinal anesthesia and, due to the lack of information, many of them interrupt breastfeeding after anesthesia. There are limited data available regarding anesthetics transfer to breast milk. This review aims to develop some considerations and recommendations based on available literature.Methods: A systematic search of the literature was conducted by using the following health science databases: Embase, Lilacs, Pubmed, Scopus, and Web of Science. The latest literature search was performed on April 6th, 2018. Additional literature search was made via the World Health Organization's website. We used the following terms for the search strategy: Anesthesia and Breastfeeding, and their derivatives.Results: In this research, 599 registers were found, and 549 had been excluded by different reasons. Fifty manuscripts have been included, with different designs of studies: prospective trials, retrospective observational studies, reviews, case reports, randomized clinical trials, case–control, and website access. Small concentrations of the most anesthetic agents, are transferred to the breast milk; however, their administration seem to be safe for lactating mothers when administered as a single dose during anesthesia and this should not contraindicate the breastfeeding. On the other hand, high-doses, continuous or repeated administration of drugs increase the risk of adverse effects on neonates, and should be avoided. Few drugs, such as diazepam and meperidine, produce adverse effects on breastfed babies even in single doses. Dexmedetomidine seems to be safe if breastfeeding starts 24 h after discontinuation of the drug.Conclusions: Most of the anesthetic drugs are safe for nursing mothers and offer low risk to the breastfed neonates when administered in single-dose. However, high-dose and repeated administration of drugs significantly increase the risk of adverse effects on neonates. Moreover, diazepam and meperidine should be avoided in nursing women. Finally, anesthesiologists and pediatricians should consider individual risk/benefit, with special attention to premature neonates or babies with concurrent diseases since they are more susceptible to adverse effects.

ResumoIntrodução: A importância e os benefícios do aleitamento materno para os bebês e para as mães estão bem estabelecidos e documentados na literatura. No entanto, é frequente que mães lactantes precisem se submeter à anestesia geral ou raquianestesia e, devido à falta de informações, muitas delas interrompem a amamentação após a anestesia. Existem poucos dados disponíveis sobre a transferência de anestésicos para o leite materno. O objetivo desta revisão foi desenvolver algumas considerações e recomendações com base na literatura disponível.Métodos: Uma busca sistemática da literatura realizada usando com os seguintes bancos de dados em ciências da saúde: Embase, Lilacs, Pubmed, Scopus e Web of Science. A pesquisa bibliográfica mais recente foi realizada em 6 de abril de 2018. Uma pesquisa bibliográfica adicional foi realizada através do site da Organização Mundial da Saúde. Usamos os seguintes termos para a estratégia de busca: Anestesia e Aleitamento materno e seus derivados.Resultados: Nesta pesquisa, 599 registros foram encontrados e 549 foram excluídos por diferentes razões. Foram incluídos 50 manuscritos, com diferentes modelos de estudo: estudos prospectivos, estudos observacionais retrospectivos, revisões, relatos de casos, ensaios clínicos randômicos, caso-controle e acesso a sites. Pequenas concentrações da maioria dos agentes anestésicos são transferidas para o leite materno; entretanto, sua administração parece ser segura para mães lactantes quando administrados em dose única durante a anestesia e isso não deve contraindicar o aleitamento materno. Por outro lado, altas doses, administração contínua ou repetida dos fármacos aumentam o risco de efeitos adversos em neonatos e devem ser evitados. Poucas drogas, como diazepam e meperidina, produzem efeitos adversos em bebês amamentados, mesmo quando administradas em doses únicas. Dexmedetomidina parece ser segura se a amamentação começar 24 horas após a interrupção do medicamento.Conclusões: A maioria dos anestésicos é segura para mães que amamentam e oferecem baixo risco para os recém-nascidos amamentados quando a administração é em dose única. No entanto, altas doses e repetidas administrações de drogas aumentam significativamente o risco de efeitos adversos em recém-nascidos. Além disso, diazepam e meperidina devem ser evitados em mulheres que amamentam. Finalmente, anestesiologistas e pediatras devem considerar o risco-benefício individual, com atenção especial para os recém-nascidos prematuros ou bebês com doenças concomitantes, pois são mais suscetíveis a efeitos adversos.
Anestesia materna deve atrasar a amamentação? Revisão sistemática da literatura
Keywords: Anesthetic drugs; Anesthetic effect; Exclusive breast feeding; Anestésicos; Efeito anestésico; Aleitamento materno exclusivo